2020
DOI: 10.1371/journal.pone.0237258
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the use of aquatic weeds as biopesticides towards promoting sustainable agriculture

Abstract: Aquatic weeds such as muskgrass (Chara spp.), water hyacinth (Eichhornia crassipes), water lettuce (Pistia stratiotes), hydrilla (Hydrilla verticillate), filamentous algae (Lyngbya wollei), and duckweed (Lemna minor) thrive in farm canals within the Everglades Agricultural Area of South Florida. Their presence, particularly during the summer months is an environmental concern with regards to water quality, in addition to being a nuisance because of their ability to multiply and spread rapidly in open waters ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The use of ethanolic extracts of Argemone ochroleuca also reduced larval feeding activity (Martínez et al, 2017). Also, biopesticides from the extracts of weed like Water lettuce reduced the survival rate of FAW by 14% while hydrilla and duckweed caused 11% and 9% reduction of FAW growth, respectively (Fu et al, 2020). Zingiber officinale and Malva sylvestris were effective causing mortality for caterpillars of FAW (Rioba & Stevenson, 2020).…”
Section: Botanicals For Managing Fawmentioning
confidence: 99%
“…The use of ethanolic extracts of Argemone ochroleuca also reduced larval feeding activity (Martínez et al, 2017). Also, biopesticides from the extracts of weed like Water lettuce reduced the survival rate of FAW by 14% while hydrilla and duckweed caused 11% and 9% reduction of FAW growth, respectively (Fu et al, 2020). Zingiber officinale and Malva sylvestris were effective causing mortality for caterpillars of FAW (Rioba & Stevenson, 2020).…”
Section: Botanicals For Managing Fawmentioning
confidence: 99%
“…Slight variations in the protocol involve inoculation of the agar containing the extract with a small volume from a liquid culture of the fungus [ 30 , 95 ] or with fungi-infected plant seeds [ 60 ] instead of an agar plug. Although the method is mostly used for fungal pathogens, Fu et al [ 144 ] employed the agar dilution method to test the antibacterial potential of water extracts from aquatic weeds against 100 bacterial strains that were inoculated on agar plates by streaking.…”
Section: Biological Activity Of Plant Extracts and Essential Oilsmentioning
confidence: 99%
“…It is observed that some plants produce allelopathic compounds which have the potential to prevent the growth, germination, survival, and reproduction of surrounding organisms. Neem (Azadirachta indica) extract kills many insects, while Eichhornia crassipes has the ability to inhibit the growth of Spodoptera litura, a lepidopteran pest [100][101][102][103]. Similarly, Chenopodium album is inhibited by the presence of duckweed and water lettuce [100].…”
Section: Biopesticides From Aquatic Plantsmentioning
confidence: 99%
“…Neem (Azadirachta indica) extract kills many insects, while Eichhornia crassipes has the ability to inhibit the growth of Spodoptera litura, a lepidopteran pest [100][101][102][103]. Similarly, Chenopodium album is inhibited by the presence of duckweed and water lettuce [100]. These examples illustrate that similar plants (or weeds) and their allelopathic chemicals have highly potent inhibitory properties against the pathogens and hence can be substituted for conventional chemical pesticides [103].…”
Section: Biopesticides From Aquatic Plantsmentioning
confidence: 99%